Isothermal Oxidation Kinetics of Iron Powders Under Vapor Atmosphere - Wenchao He; Jian Chen; Yin Deng; Zhiming Yan (Metals)
Semisteel is the byproduct of the titania slag smelting process of ilmenite concentrate with an electric furnace. To enhance the added value of semisteel, a centrifugal granulation–water curtain process was adopted to manufacture iron powders. The oxidation characteristics of granulated powders were analyzed by thermogravimetry (TG), X-ray diffraction (XRD), and scanning electron microscopy (SEM). To obtain iron powders with high purity, the isothermal oxidation kinetics of pure iron powders under vapor atmosphere were studied. TG measurements of pure iron powders were conducted at 1073 K, 1173 K, and 1273 K using a humidity generating instrument and a thermal analyzer. The results indicate that the oxidation rate increases with the increasing temperature and decreasing powder size. The entire isothermal oxidation process of iron powders with different sizes (0.3 mm < d1 < 0.35 mm, 0.4 mm < d2 < 0.45 mm, and 0.5 mm < d3 < 0.55 mm) comprises two stages. The first oxidation stage is controlled by chemical reaction; the second oxidation stage is controlled by both internal diffusion and chemical reaction. The activation energies and oxidation reaction rate equations of iron powders at different stages are calculated.